Problems of Development of Oil Fields in Eastern Siberia; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Gladkov E. A. Evgeny Alekseevich; Krasnoyarova N. A.; Shiribon A. A.; Karpova E. G. Evgenija Gennadyewna; Pham Phu Long (2018, 2018)
Title screen